On the importance of the dynamics of humour and comedy for constructionism and reflexivity in social science research methodology. Issue 5 (3rd September 2022) - Lockyer, Sharon; Weaver, Simon
ABSTRACT: Humour and comedy have gained increased significance in academic research in recent years. This article examines the importance of humour and comedy as valuable tools in qualitative social science research methodology. It makes the original contribution of utilizing humour and comedy theory, and critical understandings of both their macro and micro mechanisms and functions, to argue that humour and comedy can accommodate, and indeed, expedite, social science research methodology in relation to two key principles: constructionism and reflexivity. This represents a significant and rigorous theoretical contribution to not just humour and comedy theory but the paradigm of qualitative social science methodology. Following a review of the benefits of using humour and comedy in qualitative research, the article considers how the broader theories and more intricate mechanics of humour and comedy can facilitate research into the social world, examining how humour and comedy can inform and develop constructionism and reflexivity.